Nanoribbons self-assembled from short peptides demonstrate the formation of polar zippers between β-sheets. Issue 1 (December 2018) - Wang, Meng; Wang, Jiqian; Zhou, Peng; Deng, Jing; Zhao, Yurong; Sun, Yawei; Yang, Wei; Wang, Dong; Li, Zongyi; Hu, Xuzhi; King, Stephen; Rogers, Sarah; et al.
Abstract Peptide self-assembly is a hierarchical process, often starting with the formation of α-helices, β-sheets or β-hairpins. However, how the secondary structures undergo further assembly to form higher-order architectures remains largely unexplored. The polar zipper originally proposed by Perutz is formed between neighboring β-strands of poly-glutamine via their side-chain hydrogen bonding and helps to stabilize the sheet. By rational design of short amphiphilic peptides and their self-assembly, here we demonstrate the formation of polar zippers between neighboring β-sheets rather than between β-strands within a sheet, which in turn intermesh the β-sheets into wide and flat ribbons. Such a super-secondary structural template based on well-defined hydrogen bonds could offer an agile route for the construction of distinctive nanostructures and nanomaterials beyond β-sheets. Peptide self-assembly is a hierarchical process which includes forming β-sheets but the formation of high ordered structures remains largely unexplored. Here the authors report on a super-secondary structural template, based on well-defined hydrogen bonds by rational design and assembly of short peptides